2022
DOI: 10.1175/waf-d-21-0201.1
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Peak Wind Gusts during Specific Weather Types with the Meteorologically Stratified Gust Factor Model

Abstract: Wind gusts present challenges to operational meteorologists, both to forecast accurately and also, to verify. Strong wind gusts can damage structures and create costly risks for diverse industrial sectors. The meteorologically stratified gust factor (MSGF) model incorporates site-specific gust factors (the ratio of peak wind gust to mean wind speed) with wind speed and direction forecast guidance. The MSGF model has previously been shown to be a viable operational tool that exhibits skill (improvement over cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Previous studies have suggested that the GF model is a viable and skillful method of forecasting wind gusts when the gust factors are stratified by wind speed and wind direction [22] . They further advanced gust research by evaluating the peak wind gust predictions during several types of gust-producing weather phenomena [23] . Their results suggested that the meteorological stratified GF model performed best during high pressure and nocturnal conditions, was skillful during conditions involving snow, but failed during "rain with thunder" weather.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that the GF model is a viable and skillful method of forecasting wind gusts when the gust factors are stratified by wind speed and wind direction [22] . They further advanced gust research by evaluating the peak wind gust predictions during several types of gust-producing weather phenomena [23] . Their results suggested that the meteorological stratified GF model performed best during high pressure and nocturnal conditions, was skillful during conditions involving snow, but failed during "rain with thunder" weather.…”
Section: Introductionmentioning
confidence: 99%